ANALYSIS OF COGNITIVE METAPHOR AND METONYMY IN UZBEK - Khakimova, Muhayyo; Rahmatova, Feruza (Foreign Languages ​​in Uzbekistan (JOURNALFLEDU.COM), 2025)
This article examines how national thinking is reflected in Uzbek cognitive metaphors and metonymies through various examples. It first outlines the concept of metaphor and its types — simple, animating, synesthetic, and cognitive — emphasizing their theoretical features. The cognitive metaphor is interpreted as an essential means of understanding the world, with its formation mechanism defined through the interaction between donor and recipient domains. The main types of cognitive metaphors — structural, orientational, and ontological — are analyzed using examples from literary texts. The article provides an in-depth discussion of cognitive metaphors based on the abstraction of motion and the conceptualization of time, emphasizing the decisive role of national perception in shaping them. The term “cognitive metonymy” is introduced and explained, and its conceptual essence is clarified. It is shown that cognitive metonymy also reflects the systematic knowledge and conceptual worldview of native speakers. In cognitive metaphor, abstract and complex concepts are understood through concrete ones, facilitating the process of cognition; metaphor thus functions as an active cognitive tool, with the basis of comparison determined by national thinking. In cognitive metonymy, abstract concepts are perceived through their conceptual connections with other notions. In conclusion, both cognitive metaphor and cognitive metonymy demonstrate that concrete concepts play a crucial role in comprehending abstract notions, while the interplay between sensory and rational cognition becomes particularly evident.
Keywords: metaphor; cognitive metaphor; metonymy; cognitive metonymy; nomination; structural metaphor; orientational (referential) metaphor; ontological metaphors; national perception